DETECTION OF SOME BIOFILM FORMATION GENES AND THEIR ROLE IN ANTIMICROBIAL RESISTANCE OF UROPATHOGENIC Escherichia coli - Reyam H. A.; Aida H. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to evaluate the antimicrobial resistance, biofilm formation and some type 1 fimbriae adhesion genes. A total of 120 urine specimens were obtained from different patients with UTIs during October 2022 to February 2023 from several Baghdad hospitals. Morphological, biochemical and molecular tests were utilized for identifying E. coli isolates. The results were shown that only 80 (66.7%) of isolates were identified as E. coli. Twelve antimicrobial discs were utilized for evaluate the ability of E. coli isolate to resistant these antimicrobials. The results revealed that 98.8% of isolates were resistant to Ampicillin (AMP), followed by 81.3, 77.5, 72.5, 70, 60 and 58.8 of isolates were resistant to Cefepime (FEP), Ceftazidime (CAZ), Tigecycline (TGC), Ciprofloxacin (CIP), Trimethoprim - Sulfamethoxazole (SXT) and Aztreonam (ATM), respectively. All isolates were sensitive to Fosfomycin (FOF) and Amikacin (AMK) as well as the majority of isolates (97.5, 72.5 and 43.8%) were sensitive to Imipenem (IMP), Nitrofurantoin (NIT) and Piperacillin- tazobactam (TZP). A 50 isolates were selected as multi-drug resistant isolates. The biofilm formation of E. coli was measured using microtiter plates. The majority of isolates (55%; n=44) were moderate biofilm producers, while 38.75% (n=31) were strong producers and 5 (6.25%) were weak producers. The molecular detections of fimH and fimA genes were performed with specific primers using PCR technique. The results indicated that all isolates carry both the fimH and fimA genes.